Past Continuous Tense in the Holy Qur’an: a study in text analysis - Abdullah Ghelim , Researcher. Maysa; Lafta Hussin, Assist .Prof. Dr. Dameer (Basra studies journal, 2023)
This research sheds light on the continuity of time in past verbs and standing on the direction of continuity. The research also addresses the problem of formula (positive) time and contextual time that comes from the synergy of clues in the text. The relationship between time and formula is glimpsed when it is contextualized and its extended temporal energies are shown. The research highlighted the implicit meanings and the reason for the continuation of time through textual analysis, and the verb indicative of permanence is often attributed to God Almighty; Being eternal and ever-existing, God's actions are continuous and not limited to a single time, and this is revealed by the general context of the text. The current events in the Holy Qur’an are characterized by continuity and non-submission to the morphological time, as they come with indefinite periods of time, so they occur in multiple times. The expression of the continuous event was limited to the verb preceded by a synthetic presumption or a placeholder according to the analysis of the texts.